1997
DOI: 10.1111/j.1530-0277.1997.tb04236.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of Cytochrome P‐4502E1 and Mitochondrial Aldehyde Dehydrogenase in a Korean Population

Abstract: Mitochondrial aldehyde dehydrogenase (ALDH2) is mainly responsible for the oxidation of acetaldehyde generated during alcohol oxidation in vivo. Cytochrome P-4502E1 (CYP2E1), a liver microsomal enzyme, also metabolizes acetaldehyde and ethanol. Genetic polymorphism of ALDH2 and CYP2E1 was investigated among 481 Korean adults. A new restriction fragment-length polymorphism method was developed to determine the genotype of the ALDH2 alleles. This method proved to be simpler and faster than the hybridization meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
3
4
0
Order By: Relevance
“…Similar patterns were seen among populations from Southeast Asia and Oceania, as well as some indigenous populations in Alaska, Mexico, and Chile (24). In contrast, the ALDH2*2 null allele was frequently observed in East Asian populations, typically with 30 percent ALDH2*1/2 heterozygosity and 5-10 percent ALDH2*2/2 homozygosity (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(57)(58)(59). A similar pattern was also observed in an indigenous Brazilian population (24).…”
Section: Prevalence Of Gene Variantssupporting
confidence: 68%
“…Similar patterns were seen among populations from Southeast Asia and Oceania, as well as some indigenous populations in Alaska, Mexico, and Chile (24). In contrast, the ALDH2*2 null allele was frequently observed in East Asian populations, typically with 30 percent ALDH2*1/2 heterozygosity and 5-10 percent ALDH2*2/2 homozygosity (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(57)(58)(59). A similar pattern was also observed in an indigenous Brazilian population (24).…”
Section: Prevalence Of Gene Variantssupporting
confidence: 68%
“…Interestingly, the minor alleles of rs671 are very common in East Asians (being present in up to 50% of a given population), but less common in Caucasians 26,27 . The present study revealed an MAF for rs671 of 15.6%, which is quite consistent with previous findings from Korean populations 28,29 . The heterozygote and minor homozygotes for this SNP lead to decreased activity of ALDH2, affecting 17-35% and 1-3% of ALDH2 activities, respectively 30 .…”
Section: Discussionsupporting
confidence: 93%
“…The ALDH2*2 allele occurs mainly in oriental populations, i.e. Japanese, Chinese, inhabitants of Taiwan and Korea, and protects against developing alcoholism and alcohol liver disease 2034–37. Its role in alcohol pancreatitis was not evaluated.…”
Section: Discussionmentioning
confidence: 99%